Accelerated visualization of transparent molecular surfaces in molecular dynamics - Jurcik, Adam; Parulek, Julius; Sochor, Jiri; Kozlikova, Barbora (IEEE Pacific Visualization Symposium, 2016)
The reactivity of the biomolecular structures is highly influenced by their structural features. Thus, studying these features along with the exploration of their dynamic behavior helps to understand the processes ongoing in living cells. This can be reached by the visual representation of these processes as visualization is one of the most natural ways to convey such information. However, none of the currently available techniques provides the biochemists with an intuitive real-time representation of the dynamic movements of molecules and precise geometrical based extraction of their structural features performed instantly. In this paper we introduce such a technique enabling the user to compute and also to visualize the molecular surface along with inner voids. To obtain a better insight into the molecule, our technique enables to visualize the molecular surface transparently. The opacity can be adjusted by changing user-defined parameters in order to enhance the perception of the surfaces of inner voids. All integrated algorithms run in real-time which gives the user a big variety of exploration possibilities. The importance of our approach is even amplified with respect to the fact that currently the size of molecular dynamics simulations is increasing dramatically and offline rendering thus becomes impracticable. The usability of our technique was evaluated by the domain experts.